Nickel-catalyzed C(sp(2))-H/C(sp(3))-H oxidative coupling of indoles with toluene derivatives - Soni, V.; Khake, S. M.; Punji, B. (ACS Catalysis, 2017)
Nickel-catalyzed oxidative C(sp(2))-H/C(sp(3))-H coupling of indoles with toluene derivatives is successfully achieved in the presence of 2-iodobutane as the oxidant. This method allows the selective C-2 benzylation of indoles with toluene derivatives over the alkylation with 2-iodobutane and permits the coupling of diversified indoles via the monochelation assistance. The reaction proceeded through a single-electron-transfer (SET) process, wherein both the C-H nickelation of indole and the C-H activation of toluene derivatives have a significant effect on the entire reaction rate. The synthetic utility of this nickel-catalyzed protocol is demonstrated by the facile removal of the directing group and by the convenient synthesis of the melatonin receptor antagonist Luzindole derivatives.

Synthesis and characterization of six-membered pincer nickelacycles and application in alkylation of benzothiazole - Pandiri, H.; Sharma, D.M.; Gonnade, R.G.; Punji, B. (Journal of Chemical Sciences, 2017)
Six-membered pincer nickelacycle complexes have been synthesized and employed for the catalytic C–H bond alkylation of benzothiazole. The pincer nickelacycle, {κP, κC, κP- (2 - iPr 2POCH 2-C 6H 3- 6 -CH 2OP iPr 2)} NiBr , [(iPr4-POCCCOP)NiBr(2)] was synthesized by the reaction of 1,3 - iPr 2POCH 2-C 6H 4-CH 2OP iPr 2[(iPr4-POCCCOP)-H(1)] with (CH3CN)2NiBr2 in the presence of Et 3N via the C(2)–H activation on ligand 1. Treatment of [(iPr4-POCCCOP)NiBr](2) with AgOAc afforded the complex [(iPr 4-POCCCOP) Ni (OAc)] (3) in good yield. Both the complexes 2 and 3 were characterized by 1H , 13C and 31P -NMR spectral analysis. Further, the molecular structures of complexes 2 and 3 were established by X-ray crystallography. The complex 2 was found to be an active catalyst for the C–H bond alkylation of benzothiazole with alkyl halides containing β–hydrogen atoms. Graphical abstract: Synopsis. Six-membered pincer nickelacycles have been synthesized and structurally characterized, which show catalytic activity for the C–H bond alkylation of benzothiazole with alkyl halides containing β–hydrogen atoms.[Figure not available: see fulltext.].
Keywords: Active catalyst; Alkyl halides; Alkylation; Atoms; Benzothiazole; Benzothiazoles; Catalyst activity; Chemical activation; Crystallography; C–H activation; Hydrogen atoms; Nickelacycles; Pincer complex; Pincer complexessix-membered nickelacycle; six-membered nickelacycle; Spectrum analysis; Synthesis (chemical); Synthesis and characterizations; X ray crystallography